Cost-Effectiveness of Bivalent Respiratory Syncytial Virus Prefusion F (RSVpreF) Vaccine During Pregnancy for Prevention of Respiratory Syncytial Virus Among Infants in Argentina - Lucila Rey-Ares; Ahuva Averin; Nadia Zuccarino; Celina Guadalupe Vega; Emily Kutrieb; Erin Quinn; Mark Atwood; Derek Weycker; Amy W. Law (Infectious Diseases and Therapy, 2024)
Abstract Introduction Lower respiratory tract illness (LRTI) caused by respiratory syncytial virus (RSV) is common among young children in Argentina. Use of the currently available prophylactic agent is limited to children aged ≤ 2 years with selected high-risk conditions, and thus the majority of infants remain unprotected. We estimated the value-based price (VBP) of a novel RSVpreF vaccine for use among pregnant people for prevention of RSV-LRTI among infants during the first year of life. Methods Clinical outcomes and economic costs of RSV-LRTI during infancy and expected impact of RSVpreF vaccination during pregnancy were projected using a population-based Markov-type cohort model. Model results—estimated on the basis of gestational age at birth, disease/fatality rates, and mother’s vaccination status—include total numbers of RSV-LRTI cases, RSV-LRTI-related deaths, and associated costs. Base case analyses (RSVpreF vs. no vaccine) were conducted from the healthcare system perspective. Probabilistic sensitivity analyses (PSA; 1000 replications) were also conducted. Willingness-to-pay (WTP) was $10,636 per quality-adjusted life-year (QALY; i.e., 1 × 2021 gross domestic product [GDP] per capita) in base case analyses and PSA. Costs are reported in USD, estimated on the basis of the June 22, 2023 exchange rate. Results Use of RSVpreF among 342,110 pregnant persons provided protection to 330,079 infants at birth. In total, RSVpreF prevented 3915 RSV hospitalizations, 6399 RSV cases requiring emergency department care, 6182 RSV cases requiring a physician office visit, and 67 disease-related deaths. Direct costs were projected to be reduced by $5.0 million. With 2061 QALYs gained and vaccine administration cost of $1.4 million, the VBP of RSVpreF was estimated to be $74.46 per dose. In PSA, mean VBP was $75.02 (95% confidence interval 54.24–97.30). Conclusions RSVpreF among pregnant persons would significantly reduce the clinical and economic burden of RSV-LRTI among infants in Argentina and would be considered a cost-effective intervention up to a price of approximately $75.